Lumbosacral injuries in elite Paralympic athletes with limb deficiency: a retrospective analysis of patient records - Heneghan, N. R.; Collacott, E.; Martin, P.; Spencer, S.; Rushton, A. (BMJ Open Sport & Exercise Medicine, 2021)
Background Compared to injury data in able-bodied athletes, relatively little literature exists for Paralympic athletes. Injury data underpins the design and evaluation of injury prevention strategies in elite sport. The aim of this study was to investigate frequency, characteristics and management of lumbosacral injuries in elite athletes with limb deficiency.